Population and Family Planning : Lessons from Malawi - Prakash, Siddhartha (World Bank, Washington, DC, 2012)
The objective of the Population and Family Planning (FP) Project, a Learning and Innovation Loan (LIL), was to test the feasibility of a comprehensive and district-wide Community Based Distribution (CBD) approach to Population and Family Planning Services in three districts, thereby increasing the Contraceptive Prevalence Rate (CPR) for modern methods. Rigorous testing of the hypothesis was ensured in the design by selecting control districts and using the same instruments to collect both the baseline and end of project data. The three rural pilot districts - Chitipa, Ntchisi and Chiradzulu, represented the three mains regions of North, South and Central Malawi and were adjacent to the control ones with which they shared comparable socio-demographic characteristics such as household composition (female headship and number of residents), environmental exposure (water sources, latrines) and backgrounds of respondents (age, education, marital status).